Penerapan Internet Of Things Untuk Memantau Aktivitas Jantung Berbasis Android - Priyulida, Fitri; B Fona; Eriansyah Putra; Situmorang, Harold (Jurnal Mahajana Informasi, 2023)
The monitoring system of the heart's electrical activity is the basis of the electrocardiograph (ECG) in monitoring the condition of the heart, the ECG series consists of biopotential amplifiers from an ECG instrument which is the main component in this study, recording cardiac activity is still a burden for the medical world in the use and results of the expected output. From the results of research conducted on the heart rate graph (BPM) at the Medan Health Facility Security Center, the results of research were obtained using the MPS450 multiparameter simulator, where when changes were made to the signal gradually changes in values at 60, 80, 100, 120, 150, 180, 200, 220 had a distance change in time in sending and receiving data displayed on the android monitor screen (LCD). The results issued by android are graphic displays that can be saved in the form of images in JPEG format periodically or real time so as to facilitate and reduce the use of